Design and Analysis of the Low Cost Induction Gear for Vertical Axis Wind Turbines - Mysiński, Michał; Jędryczka, Cezary; Macyszyn, Łukasz (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
This paper investigates the concept of induction gear based on eddy current phenomena. In the research, impact of the selected dimensions of the magnetic circuit on the electromagnetic torque and gear estimated efficiency has been examined. Numerical models that employ the finite element method have been developed to determine the electromagnetic performance of variants studied. On this basis, the best design solutions were identified for future studies.